Dynamics of phytoplankton communities around the Antarctic Peninsula and off the portuguese coast - Mendes, Carlos Rafael Borges (2012)
Tese de doutoramento, Biologia (Ecologia), Universidade de Lisboa, Faculdade de Ciências, 2012